Psychological care in an isolation center in times of COVID-19 - Mónica González Brito; Yolanda Cabrera Macías (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2021)
The current situation generated by the COVID-19 pandemic affects all human beings, mainly those linked to people who are sick or infected by the virus. Psychology professionals in the national and international context contribute their knowledge and provide help to patients and health personnel. The article aims to expose the experiences of psychological care in an isolation center for contact persons of patients with COVID-19.